2001
DOI: 10.1523/jneurosci.21-16-06045.2001
|View full text |Cite
|
Sign up to set email alerts
|

IPSC Kinetics at Identified GABAergic and Mixed GABAergic and Glycinergic Synapses onto Cerebellar Golgi Cells

Abstract: In the rat cerebellum, Golgi cells receive serotonin-evoked inputs from Lugaro cells (L-IPSCs), in addition to spontaneous inhibitory inputs (S-IPSCs). In the present study, we analyze the pharmacology of these IPSCs and show that S-IPSCs are purely GABAergic events occurring at basket and stellate cell synapses, whereas L-IPSCs are mediated by GABA and glycine. Corelease of the two transmitters at Lugaro cell synapses is suggested by the fact that both GABA A and glycine receptors open during individual L-IPS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
175
1
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(182 citation statements)
references
References 70 publications
(95 reference statements)
4
175
1
2
Order By: Relevance
“…On their way, these longer axons may even course through the white matter (Laine and Axelrad 1996). As direct targets of Lugaro cells, basket and stellate cells have been identiWed only by morphological means (Laine and Axelrad 1998), whereas the projections of Lugaro cells onto Golgi (Dieudonne and Dumoulin 2000;Dumoulin et al 2001;Dieudonne 1995) and Purkinje cells (Dean et al 2003) have been analyzed functionally. It has been estimated that one Lugaro cell projects to more than 100 Golgi cells (Dieudonne and Dumoulin 2000); comparable numerical estimates for the Lugaro to Purkinje cell, or Lugaro to basket/ stellate cell projections are not available.…”
Section: Large Inhibitory Interneurons Of the Granule Cell Layermentioning
confidence: 99%
See 1 more Smart Citation
“…On their way, these longer axons may even course through the white matter (Laine and Axelrad 1996). As direct targets of Lugaro cells, basket and stellate cells have been identiWed only by morphological means (Laine and Axelrad 1998), whereas the projections of Lugaro cells onto Golgi (Dieudonne and Dumoulin 2000;Dumoulin et al 2001;Dieudonne 1995) and Purkinje cells (Dean et al 2003) have been analyzed functionally. It has been estimated that one Lugaro cell projects to more than 100 Golgi cells (Dieudonne and Dumoulin 2000); comparable numerical estimates for the Lugaro to Purkinje cell, or Lugaro to basket/ stellate cell projections are not available.…”
Section: Large Inhibitory Interneurons Of the Granule Cell Layermentioning
confidence: 99%
“…Whereas the Lugaro cell input to Golgi cells has mixed GABAergic and glycinergic components (Dumoulin et al 2001), their input to (juvenile; analyzed at postnatal day 14 in the rat) Purkinje cells is mediated only by GABA A receptors (Dean et al 2003). (Adult) Purkinje cells do express glycine receptors (Triller et al 1987), though these are rather sparsely localized on main dendritic shafts.…”
Section: Large Inhibitory Interneurons Of the Granule Cell Layermentioning
confidence: 99%
“…The specificity of transmission in their postsynaptic targets is ensured by the differential expression of receptors. Thus, spontaneous IPSCs in granule cells are mediated selectively by GABA A receptors (39), whereas Golgi cells, Lugaro cells, unipolar brush cells, and possibly other interneurons exhibit either glycinergic or mixed glycinergic/GABAergic currents ( Figure 1) (42,43). At least in Golgi cells, GABA A and glycine receptors can co-exist within a given postsynaptic site (42).…”
Section: Organization Of Gaba a Receptors In The Cerebellar Cortexmentioning
confidence: 99%
“…Omission of the primary antibody served as a negative control to ensure the specificity of labeling. The specificity of this antibody has been thoroughly characterized to confirm its selectively for GlyR subunits (Pfeiffer et al 1984) and has been extensively used in anatomical localization studies (e.g., Dumoulin et al 2001;Tsen et al 2000). Stained cells were observed with a confocal laser-scanning microscope equipped with appropriate filters.…”
Section: Glyr-like Immunohistochemistrymentioning
confidence: 99%
“…Elegant electrophysiological recordings from motoneurons in spinal cord and brain stem slices show that miniature IPSCs are mediated by the activation of both receptors, demonstrating cotransmission of these two inhibitory neurotransmitters (Jonas et al 1998;O'Brien and Berger 1999). A recent study in cerebellar slices has also demonstrated GABA and glycine co-release at synapses onto Golgi cells (Dumoulin et al 2001). However, in recordings from identified lamina I neurons in spinal cord slices, it appears that although glycine and GABA are coreleased, GABA A Rs seem to be located extrasynaptically because the GABA A Rmediated component of the synaptic current is observed only following large but not minimally evoked monosynaptic IPSCs (Chery and de Koninck 1999).…”
Section: Are Glyrs Involved In Fast Inhibitory Transmission In Hippocmentioning
confidence: 99%